Long Noncoding RNA-H19 Contributes to Atherosclerosis and Induces Ischemic Stroke via the Upregulation of Acid Phosphatase 5 - Huang, Yujing; Wang, Liping; Mao, Ying; Nan, Guangxian (Frontiers in Neurology, 2019)
Objective: Atherosclerosis is closely associated with ischemic stroke, and long noncoding RNA-H19 (lncRNA-H19) might be a potential target for treating atherosclerosis. The present study aimed to investigate the function of lncRNA-H19 in atherosclerosis and to explore a novel therapeutic strategy for ischemic stroke. Methods: Differentially expressed genes (DEGs) in atherosclerosis were screened by searching public database. In combination with the lncRNA-H19-knockout database, potential lncRNA-H19-mediated gene was retrieved and their relationship was identified. In order to assess the detailed regulatory mechanism of lncRNA-H19, we used a lentivirus packaging system to upregulate Acp5 (Acid phosphatase 5) expression in vascular smooth muscle cells (VSMC) and human umbilical vein endothelial cells (HUVECs). The expression of ACP5 was determined by Western Blot, and evaluations of cell proliferation and apoptosis were detected. An ischemic stroke mouse model was established. Atherosclerosis was measured by using plaque area size. The effects H19 on the expression of ACP5 were explored by the overexpression or silence of H19. Results: H19 and ACP5 were associated with Acute Stroke Treatment (TOAST) subtypes of atherosclerotic patients. The target prediction program and dual-luciferase reporter confirmed ACP5 as a direct target of H19. Lentivirus-mediated H19-forced expression upregulated ACP5 protein levels, promoted cell proliferation and suppressed the apoptosis. The plaque area size was larger in ischemic models than controls. The overexpression or silence of H19 increased or reduced the plaque size. The overexpression or silence of H19 resulted in the expression or inhibition of ACP5. Conclusion: IncRNA-H19 promoting ACP5 protein expression contributed to atherosclerosis and increased the risk of ischemic stroke.